2018
DOI: 10.1155/2018/7814206
|View full text |Cite
|
Sign up to set email alerts
|

Households Sociodemographic Profile as Predictors of Health Insurance Uptake and Service Utilization: A Cross-Sectional Study in a Municipality of Ghana

Abstract: Introduction. Attempts to use health insurance in Low and Middle Income Countries (LMICs) are recognized as a powerful tool in achieving Universal Health Coverage (UHC). However, continuous enrolment onto health insurance schemes and utilization of healthcare in these countries remain problematic due to varying factors. Empirical evidence on the influence of household sociodemographic factors on enrolment and subsequent utilization of healthcare is rare. This paper sought to examine how household profile influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
17
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 25 publications
(100 reference statements)
9
17
4
Order By: Relevance
“…The study showed that the marital status plays significant role in utilizing social health insurance scheme and married household were more utilizing the schemes than the singles. 8 Indicators like ethnicity, religion showed no significant relationship in the enrollment of the social health insurance scheme as it basically focus on the household level than the individual level.…”
Section: Resultsmentioning
confidence: 98%
“…The study showed that the marital status plays significant role in utilizing social health insurance scheme and married household were more utilizing the schemes than the singles. 8 Indicators like ethnicity, religion showed no significant relationship in the enrollment of the social health insurance scheme as it basically focus on the household level than the individual level.…”
Section: Resultsmentioning
confidence: 98%
“…A study in Nambia concluded that sociodemographic factors (sex, education, and wealth) are associated with universal health care and financial coverage (45). Another study in Ghana also concluded that sociodemographic conditions (elders, women, poor education, and marginalized population) were associated with health services and financial coverage (46). Similar types of study in Vietnam showed that sociodemographic factors influenced health care service and patients satisfaction (47).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also confirmed the role of ethnicity in determining the enrolment of households in the health insurance schemes. 32,40,41 Evidences from studies in various LMICs have shown a positive association between wealth or socio-economic status and health insurance uptake. 34,35,42,43 Bivariate and multivariate analyses in this study also confirmed a similar association.…”
Section: Discussionmentioning
confidence: 99%